The Treaties of Karlowitz and Russia’s attitude toward the „Eastern Question” - Peltz, Wojciech (Balcanica Posnaniensia. Acta et studia, 2003)
The aim of the article is to show how events at the end of the 17th century, especially the peace conference in Karlowitz, initiated a new direction in Russian policy – the pursuit of leadership over the Orthodox population and the gradual undermining of the Ottoman Empire's influence in South-Eastern Europe. The author analyses the origins of the Russian belief in the special civilisational and religious role of Russia – the „Third Rome” – which reflected the imperial aspirations of the tsarist regime. The article draws on a wide range of historical sources – Russian, Turkish, Western European – and numerous academic studies. The conclusions show that the Karlowitz treaties did not bring Russia all the expected territorial benefits, but they did mark the beginning of the country's lasting presence in the Balkan power games. Russia systematically used the postulate of protecting Orthodox peoples as a tool of political influence and a justification for further military interventions.